If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 11) * 2 = 64 Reorder the terms: (11 + X) * 2 = 64 Reorder the terms for easier multiplication: 2(11 + X) = 64 (11 * 2 + X * 2) = 64 (22 + 2X) = 64 Solving 22 + 2X = 64 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 2X = 64 + -22 Combine like terms: 22 + -22 = 0 0 + 2X = 64 + -22 2X = 64 + -22 Combine like terms: 64 + -22 = 42 2X = 42 Divide each side by '2'. X = 21 Simplifying X = 21
| f(x)=raiz(x) | | (X+8)2=4 | | 0.2x-3=0 | | 7q(x+4q)=11 | | 4x^2-10=110 | | 35=7x+7(-3x-17) | | 20=4n+8 | | -10x=13-(-17) | | (Y-8)*y=200 | | 95=5b | | 2200= | | h(x)=raiz(x-1) | | Ab+4a-5b-20= | | 3p-p/4=76 | | 32*tan(29)=x | | (6q+1)+4q+q=2.9 | | 32*tan(/9) | | (2-z)(4z+7)=0 | | 8x^4y+56x^2y^2-72x^2y= | | 2(27m^3+1)=0 | | 12a^2+11a+15=0 | | X^2+2x^2=sqrt(80) | | x^3+6x^2+9x-8=0 | | 36-9x-x^2=0 | | sen^2(x)+2=cos^2(x)+3sen(x) | | log(8)4x^2-log(8)9=2 | | 18a^2b^7+9ab^3-63ab^7= | | 3r^2+3r+0=0 | | 54m^3+2=0 | | 13-(2c+12)=2(c+2)+3c | | 2n-n/2=54 | | 5+m^3+2=0 |